FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN BENSIN SUPER tt: STUDI KASUS DI DKI JAKARTA (PERIODE APRIL 1997 - DESEMBER 1999) - Vigi Anggaputri; SIwi Nugraheni (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
The main source of air pollution in DKI Jakarta came from gas emission of vehicles. One of the pollutants which came from exhaust motorized vehicle is lead (Pb) which contributes to the biggest lead pollution in the air. Lead (Pb) is known as a harmful pollutant this paper will focus on the factors influence unleaded gasoline sales, well known as the